Pragmatisme Instrumental dalam Sketsa Pendidikan Islam di Indonesia - Hendro Widodo (Edukasia Islamika : Jurnal Pendidikan Islam, 2019)
This article aims to provide both theoretical and practical lenses on sketches of Islamic education portrayed in Indonesia in an instrumental pragmatism paradigm. The style of Islamic education in Indonesia is implemented in a pragmatic-instrumental pattern, which is viewed in the practical application of the learning process in formal educational institutions, regarding the educational objectives, the concept of the teacher, and the methods of learning. The present study suggests that pragmatism-in-style education has placed humans as the measure of everything. Education is intended not only to receive meaningful knowledge but also to escalate beneficial skills. It gives an equal portion of what will be achieved in the world and the hereafter. It is worth mentioning that the concept of the balance of the hereafter is relevant to national education goals. They constitute the development of the students’ potential to become human beings who believe in and fear God Almighty, noble, healthy, knowledgeable, capable, creative, independent and democratic and responsible. It depicts that education becomes an instrument to promote all aspects of human potential.